Penyesuaian Perkawinan Pasangan Suami-Istri Dewasa Muda Ditinjau Dari Kecerdasan Emosional dan Umur Perkawinan - Wahyuningsih, Hepi (Faculty of Psychology, Universitas Surabaya, 2005)
The research is aimed at examining the role of emotional intelligence and length of marriage in predicting marital adjustment among married couples at young adulthood. Proposed hipothesis were: (1) There is relationship among emotional intelligence, length of marriage and marital adjustment for husbands; (2) There is relationship among emotional intelligence, length of marriage and marital adjustment for wives. The subjects of this research were 49 couples, in their first marriage, the average length of marriage was 8.9 years, 100%ofhusbands were employed and 55.1%ofwives were employed. All subjects had completed high school. The data collection was done using DAS (Dyadic Adjustment Scale) and Emotional Intelligence Scale. Hypothesis were tested by regression analysis . The results indicated that there was relationship among emotional intelligence, length of marriage and marital adjustment for husbands and wives. Emotional intelligence is an significant predictor of marital adjustment for husband (b= 324; p= .023< .05) and wives (b=.334; p=.019<.05). Length of marriage however is not a significant predictor for marital adjustment. It also was found that no differences among roles in marriage and employment status of wives in marital adjustment. Penelitian ini bertujuan menguji peran kecerdasan emosional dan umur perkawinan dalam memprediksi penyesuaian perkawinan yang dimiliki suami maupun istri pada masa dewasa muda. Subjek penelitian (N=49) adalah pasangan suami-istri, baru pertama kali menikah, rata-rata usia perkawinan 8,9 tahun, 55.1% istri bekerja, dan tingkat pendidikan subjek SMA ke atas. Data diperoleh dari Skala Penyesuaian Perkawinan dan Skala Kecerdasan Emosional, dan diuji dengan analisis regresi . Hasil-hasil menunjukkan ada hubungan antara kecerdasan emosional dan usia perkawinan dengan penyesuaian perkawinan suami, dan antara kecerdasan emosional dan usia perkawinan dengan penyesuaian perkawinan istri. Kecerdasan emosional mampu menjadi prediktor baik bagi penyesuaian perkawinan suami maupun istri, sedangkan usia perkawinan tidak, baik pada suami maupun istri. Hasil penelitian juga menunjukkan tidak ada perbedaan penyesuaian perkawinan baik berdasarkan status istri maupun status dalam perkawinan. Didiskusikan juga mekanisme pertahanan ego dan sebab-sebab lain yang mendasari hasil-hasil terebut.